#BlackLivesMatter and business: A way forward for equality and diversity in the workplace. Issue 2 (12th March 2018) - Unknown
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: For any student of political philosophy, they are taught there are three types of justice delivered to deserving criminals. Retributive justice, which is based on a punishment that may – or may not in some cases – fit the crime. Then there is distributive justice, which focuses instead on the rehabilitation of the offender and will also include treatment rather than punishment. Finally, there is retributive justice which despite its relative newness as a term has been referred to and used on a small scale all the way back to biblical times and beyond. Practical implications: The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.